Analisis Pengaruh Faktor Psikologis Wisatawan Pada Keputusan Berkunjung - Cokorda Krisna Yudha; I Gusti Agung Prama Yoga; I Made Chandra Mandira (Universitas Kadiri, 2021)
Bali is one of the tourism barometers in Indonesia which also supports the Indonesian economy. Various strategic steps were taken to attract tourist visits to Bali. Interest will lead as consideration for a tourist to make various tourism decisions, one of which is visiting decisions. The decision to visit can be influenced by several factors, one of them is influenced by psychological factors of tourist as a consumer. Psychological factors are a person's internal processes that exist within the consumer itself which consists of motivation, perception, attitude, learning and personality that have a very strong influence on consumers in making purchasing decisions which in this study are visiting decision making. Data collection was carried out by using a questionnaire method which was distributed to the respondents. Respondents of this study were domestic tourists who visited the Neka Museum in 2020. Based on the results of data analysis using multiple linear regression analysis, it was found that motivation, attitudes, perceptions, and personality had a positive and significant effect on visiting decisions. Learning variables do not have a significant effect on visiting decisions.